Development and evaluation of a generic population pharmacokinetic model for standard half-life factor VIII for use in dose individualization - McEneny-King, Alanna; Chelle, Pierre; Foster, Gary; Keepanasseril, Arun; Iorio, Alfonso; Edginton, Andrea N. (Journal of pharmacokinetics and pharmacodynamics, 2019)
Hemophilia A is a rare bleeding disorder resulting from a lack of functional factor VIII (FVIII). Therapy consists of replacement with exogenous FVIII, but is complicated by high inter-patient variability. A population pharmacokinetics (PopPK) approach can facilitate the uptake of an individualized approach to hemophilia therapy. We developed a PopPK model using data from seven brands of standard half-life FVIII products. The final model consists of a 2-compartment structure, with a proportional residual error model and between-subject variability on clearance and central volume. Fat-free mass, age, and brand were found to significantly affect pharmacokinetic (PK) parameters. Internal and external evaluations found that the model is fit for Bayesian forecasting and capable of predicting PK for brands not included in the modelling dataset, and useful for determining individualized prophylaxis regimens for hemophilia A patients.